PLOSOWAHYU's INTEGRATED REST AREA PROMOTES A SUSTAINABLE COMMUNITY - Ruswaji Ruswaji; Puguh Cahyono; Heri Suprapto; Dika Efendi; Rima Dwi VP (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Plosowahyu Village is one of the villages in the Lamongan district. There are 3 hamlets, namely Plalangan Hamlet, Plosogeneng Hamlet and Wahyu Hamlet. Administratively, Plosowahyu village is divided into 12 RT and 3 RW. Each is under the leadership of the RT and RW heads. Plosowahyu Village is categorized as an Independent Village, namely an Advanced Village that has the ability to carry out village development. The physical development of Plosowahyu village potential is a sustainable development plan for the Plosowahyu village rest area which aims to improve the community's economy. As well as spearheading the empowerment of all aspects of integrated business activities with the support of increasingly sophisticated information technology, through the application of Management Information Systems in village governments and existing economic institutions, including Bumdes and existing MSME groups. The Plosowahyu village rest area will be one of the mini tours that is very pleasant for visitors and the community where there are stalls and also stalls for people who have local MSMEs for visitors to the rest area and floating houses in the middle of the lake which are a good feel for visitors in the area. participate in the BUMDES office, as well as educational tours with the Etawa goat farm which is also the icon of the rest area. So that it will increase the selling power of the rest area itself. For the manager, the Plosowahyu Village Rest Area is an integrated business that will not only generate income from a financial perspective, but must be balanced with effective, efficient and professional maintenance and management methods from upstream to downstream, so as to provide optimal services for the community. its users. If consumers already feel satisfied with the use of the available facilities, then this will make a return for the manager's income. For researchers, the Plosowahyu Village Rest Area will provide useful outcomes in scientific studies in the form of journals, intellectual property rights and other scientific works as well as contribute to improving community welfare.